PSIKOLOGI PENDIDIKAN ISLAM SEBAGAI PILAR PEMBENTUKAN KARAKTER ISLAMI PESERTA DIDIK - Firanita Putri; Rodhatul Jennah; Hamidah (STKIP Subang, 2025)
Islamic Educational Psychology plays a strategic role in shaping the Islamic character of students because it views humans as beings with physical, psychological, and spiritual dimensions. This article aims to examine the concepts, roles, and strategies of Islamic Educational Psychology as a pillar in shaping the Islamic character of students. This study uses a qualitative approach with a library research method, sourced from the Qur'an, Hadith, and various scientific literature in the form of books and journals relevant to the themes of educational psychology and Islamic character education. Data collection techniques were carried out through documentation studies, while data analysis used descriptive-analytical methods. The results of the study show that Islamic Educational Psychology contributes significantly to shaping Islamic character through an understanding of the psychological development of students, the instilling of the values of monotheism, the habit of worship, the exemplary behavior of educators, individual and humanistic approaches, and the integration of Islamic values in the learning process. In addition, the role of educators as agents of character building is a key factor in instilling moral, spiritual, and social values in students. Thus, Islamic Educational Psychology can serve as a conceptual and practical foundation for shaping students who are not only intellectually superior, but also have an Islamic personality with good character and are able to face the challenges of education in the modern era.